Facing cyber threats head on protecting yourself and your business - Minick, Brian (Rowman & Littlefield Publishers, 2016)
Facing Cyber Threats Head On explains battle against hackers as a fight between people, not technologies. Brian Minick offers a new approach to defending against cyber attacks, one that balances business risk with the cost of creating defenses that can change as quickly and often as attackers can.